The Role of Project-Based Learning in Fostering Students’ Writing Creativity: A Perception-Based Study - Sitti Hawaena; Nurhaya; Andi Adisaturrahimi (FOSTER: Journal of English Language Teaching, 2025)
The purpose of this study is to examine students' perceptions of the effectiveness of Project-Based Learning (PBL) in enhancing creative writing skills. Utilizing Robbins' framework of perception—acceptance, understanding, and evaluation—this research employs a qualitative methodology. The participants consisted of twenty students selected purposively from a larger literacy organization at STKIP ABMUL, Dampal Selatan. Data collection instruments included observational checklists and semi-structured interviews. The findings reveal that the PBL model significantly contributes to the improvement of students' writing abilities, particularly in fostering creativity, imagination, and critical thinking. The participants expressed increased motivation and interest in writing, particularly in crafting short stories. As an outcome of their engagement with PBL, a student-initiated literacy organization was formed, serving as a collaborative space to nurture creative expression through written work.